Pengaruh Brand Equity Pada Niat Beli Konsumen Apartemen Taman Rasuna - , Reynold M. Sihombing, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Effect of Brand Equity on Consumer Purchasing Intention Taman Rasuna Apartments. This study aims to determine the effect caused by brand awareness and Brand Association on purchase intention Taman Rasuna apartment. The data used are primary data obtained through questionnaires. Questionnaires distributed to 100 respondents. Test instrument carried out using validity and reliability. The data were analyzed using multiple regression analysis with SPSS program. The results showed that brand awareness had no significant effect on consumer purchase intention. While the brand associations have significant influence on purchase intentions. Together these two variables affect consumer purchase intentions significantly. These results indicate that there is a discrepancy between the results of research on brand awareness with current research. This discrepancy leads to the insignificant effect between brand awareness and purchase intentions. This happened on luxury products such as brand awareness prospective apartment where consumers do not affect the purchase intention toward the product.